Balancing the books: Kansas' water past, present and future - Barfield, David (Kansas State University, 2009)
This presentation examines the historical development of water resources in Kansas and the progression of state water law and regulations from the water development phase toward sustainability; the current status of water supplies and demands in various parts of Kansas; and steps being taken or considered to maintain or advance toward long-term sustainable water supplies while maximizing beneficial use of this vital resource.
Keywords: Water resources; Historical development; Kansas; Current status